Optimization of Process Variables in 3D Printing on Dimensional Accuracy Using Nylon Filaments - Hasdiansah Hasdiansah (IJNMT (International Journal of New Media Technology), 2022)
Abstract—Manufacturing process over the past 50 years has led to very rapid and continuous progress in the manufacturing industry, one of the manufacturing processes that has progressed is 3D printing technology. The type of filament used in this research is nylon filament. This study aims to obtain optimal process parameters for dimensional accuracy. The method used in this study is the Taguchi L27 OA method. The process parameters used are nozzle temperature, bad temperature, layer thickness, flowrate, printing speed, overlap, infill density, infill speed, wall thickness. The results showed that the optimal process parameters are nozzle temperature(256°C), bad temperature(96°C), layer thickness(0.2mm), flowrate(90%), printing speed(30mm/s), overlap (10%), Keywords: 3D printing; Accuracy; Dimensions; Nylon; Parameter;